Relationships between lung volume and respiratory muscle performance in triathletes - Boussana, A.; Galy, O.; Le Gallais, D.; Hue, O. (Medicina dello Sport, 2020)
BACKGROUND: Increase or decrease in lung volumes has been reported following short bouts of high-intensity exercise, and prolonged, moderate intensity exercise, and attributable to the decrease on respiratory muscle strength and endurance. This study investigated whether a change in initial lung volume influences the decrease in respiratory muscle performance in triathletes during a cycle-run succession (C-R). METHODS: Thirteen male triathletes performed a two-trial protocol: 1) an incremental cycle exercise to assess maximal oxygen uptake (VO2max); and 2) combinations of cycling (20 min) and running (20 min) performed at 75% of VO2max. Spirometry test was performed at rest and immediately after cycle-run succession. Respiratory muscle force was assessed by measuring maximal expiratory (PEmax) and inspiratory (PImax) pressures before and 10 min after C-R. Lastly, respiratory muscle endurance was measured 1 day before and 30 min after C-R. RESULTS: The results showed a significant decrease in forced vital capacity (FVC) and significant increases in residual volume (RV) and in functional residual capacity (FRC) (P<0.05). Maximal inspiratory pressure (134.92±5.0 cmH2O versus 127.69±7.2 cmH2O) and endurance time limit (5.38±0.4 min versus 3.45±0.4 min) were decreased post-cycle-run succession compared with pre-cycle-run succession (P<0.001). Interestingly, we found a significant correlation between pre- versus post-cycle-run succession forced vital capacity and residual volume (r=0.60, P<0.02). CONCLUSIONS: The cycle-run succession induced respiratory muscle fatigue. However, the lack of correlation suggests that the decrease in the respiratory muscles` performance is still not responsible for changes in lung volumes, but could be explained by other phenomena.